969 MID AND LONG TERM ATRIO-VENTRICULAR MECHANISM IN CHILDREN AFTER RECOVERY FROM ASYMPTOMATIC O MILDLY SYMPTOMATIC SARS COV2 INFECTION. (15th December 2022) - Cuppini, Elena; Sabatino, Jolanda; Gozzi, Anna; Cattapan, Irene; Di Candia, Angela; Di Chiara, Costanza; Sirico, Domenico; Donà, Daniele; Fumanelli, Jennifer; Basso, Alessia; Pogancik, Pietro; Castaldi, Biagio; et al.
Abstract: Background: Clinical manifestations of children's coronavirus disease-2019 (COVID-19) were initially considered less severe compared with adult patients. However, there is now increasing evidence of a "long-tail" of COVID-19 related symptoms lasting for several months after recovery from the acute infection. Long COVID-19-related symptoms and mechanisms are poorly characterized and understood, with several phenotypes reported, often driven by long-term tissue damage (such as lung, heart and brain) and pathological inflammation due to viral persistence and/or immune deregulation. Purpose: The objective of this study was to evaluate atrio-ventricular mechanics, by means of two-dimensional speckle-tracking echocardiography, in previously healthy children recovered from asymptomatic or mildly symptomatic severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection in a long-term follow-up. Methods: We analysed a cohort of 157 paediatric patients, mean age 7 ± 4 years, who had a confirmed diagnosis of SARS-CoV-2 infection and were asymptomatic or mildly symptomatic for COVID-19. Patients underwent standard transthoracic echocardiogram and speckle tracking echocardiographic study 148 ± 68 days after diagnosis. One hundred seven age, sex, and body surface area comparable healthy subjects were used as control group. Results: Left ventricular ejection fraction was within normal limits in postCOVID-19 cases and CTRL with no significant differences between the two groups (postCOVID-19: 65.6 ± 4% vs CTRL: 65.0 ± 5%, p = 0.182).Left ventricular (LV) global longitudinal strain (postCOVID-19: -20.5 ± 2.9%; CTRL: -21.8 ± 1.7%; p < 0.001) was significantly reduced in cases compared with CTRLs. An amount of 11 (7%) postCOVID-19 cases showed impaired GLS values < -17% and 95 subjects (60%) presented with a strain lower than -16% in more than 2 segments. These subjects did not show any difference regarding symptoms or serological findings. Moreover, GLS was significantly reduced in children with disease's onset during the second wave of COVID-19 pandemic, compared with those during the first wave (second wave: -20.2 ± 2.6%; first wave: -21.2 ± 3.4%; p = 0.048). Finally, peak left atrial systolic strain was within the normal range in the postCOVID-19 group with no significant differences compared to CTRL (postCOVID-19: 49.1 ± 12%; CTRL: 49.5 ± 18%). Conclusions: SARS-CoV-2 infection may affect left ventricular deformation in children despite an asymptomatic or only mildly symptomatic acute illness. Our data show an amount of 60% of children, recovering from asymptomatic or mildly symptomatic COVID-19, with still mild subclinical systolic cardiac impairment in the mid- and long-term follow-up after the infection. This subtle impairment was seen to be worse in children recovering from the second wave of COVID-19 compared to the first one. A follow-up is needed to verify the reversibility of these alterations and their impact on long-term outcomes.